Modifikasi Alat Pemotong Nata De Coco Semi Otomatis - Sulharman Sulharman (Balai Riset dan Standardisasi Industri Samarinda, 2016)
Modification was clipper of nata de coco with system work appliance owning knife block of athwart and lengthwise direction by using conveyor as conductor of nata de coco.Clipper modification of nata de coco consist of 3(three) part of : knife block as part of functioning cut nata (knife block consist of 2 part of that is part of athwart and lengthwise), conveyor as conductor of nata de coco step into knife block, and workbench as part of uniting knife block and of conveyor. From result of test of performance appliance got crosscut ability 182 kg/hour.Difference of appliance capacities before and after modified equal to 1.4 times or there is 45,6 %. Energy at this appliance equal to 1300 watt. Tecno economic to the effort nata de coco by using this clipper is value of BEP Rp.160.310.850,7..percentage of BEP 35,28%.capacities 246,63 kg with time return capital 2,5 year.